2014
DOI: 10.2147/opth.s54578
|View full text |Cite
|
Sign up to set email alerts
|

One-year results of intravitreal ranibizumab combined with reduced-fluence photodynamic therapy for polypoidal choroidal vasculopathy

Abstract: PurposeTo compare the 1-year results of intravitreal ranibizumab combined with reduced-fluence photodynamic therapy (RF-PDT) to intravitreal ranibizumab (IVR) alone for eyes with polypoidal choroidal vasculopathy (PCV).MethodsWe reviewed the medical records from 47 consecutive patients with PCV (47 naïve eyes). Seventeen eyes from 17 patients had one IVR treatment combined with RF-PDT followed by two additional IVR treatments (combined group), and 30 eyes from 30 patients were treated with 3 monthly IVR treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…However, retinal hemorrhage, RPE tear and other complications have been reported to be associated with PDT in the treatment of PCV (9). Ranibizumab may reduce lesion leakage and improve or stabilize visual acuity in patients with PCV (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, retinal hemorrhage, RPE tear and other complications have been reported to be associated with PDT in the treatment of PCV (9). Ranibizumab may reduce lesion leakage and improve or stabilize visual acuity in patients with PCV (19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, photodynamic therapy (PDT) has also been demonstrated to effectively seal the blood vessels in PCV, and subsequently limit lesion development (6,7). However, long-term follow-up observations have indicated a higher recurrence rate and retinal hemorrhage incidence following PDT, and therefore repeated treatments are required (8,9). By contrast, combination therapy with intravitreal ranibizumab (IVR) injection and PDT has been demonstrated to have more satisfactory outcomes, which may significantly reduce the incidence of complications (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the risk of complications using standard PDT, less intensive protocols for PDT treatment have been suggested. They include reducing the dose of verteporfin administered or reducing one of the laser parameters (dose rate or duration of laser application) to achieve a reduction in the laser fluence (light dose) [13][14][15][16][17][18][19][20]. Various authors have described treatment success with these less intensive protocols which theoretically reduces the risk of complications [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They include reducing the dose of verteporfin administered or reducing one of the laser parameters (dose rate or duration of laser application) to achieve a reduction in the laser fluence (light dose) [13][14][15][16][17][18][19][20]. Various authors have described treatment success with these less intensive protocols which theoretically reduces the risk of complications [13][14][15][16][17][18][19][20]. Several studies have reported the success of reduced-fluence PDT in the treatment of PCV [13][14][15][16][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation